A Case Report on Acute Suppurative Thyroiditis - Oluwayemi, I. O.; Abduraheem, F. O.; Agaja, O. T.; Oke, O. J.; Ogundare, E. O.; Ajite, A. B.; Olatunya, O. S. (Highlights on Medicine and Medical Research Vol. 11, 2021)
Acute suppurative thyroiditis is a rare but potentially life-threatening endocrine emergency. It represents 0.1 to 0.7% of surgically-treated thyroid pathologies. We report a case of 3 years 11 month old girl who was brought to the hospital by her parents with a history of painful anterior neck swelling of one week duration which was initially the size of the distal phalanx of the child’s middle finger and progressively increased to occupying most of the anterior neck. There was a preceding history of fish bone impaction while eating 2 weeks earlier. Within 24 h of admission child was noticed to be febrile (temperature 38.5°C), she had dysphagia, hoarseness and limitation in movement of the head. No history or clinical features suggestive of hyper- or hypothyroidism. Anterior cervical lymph nodes were enlarged and tender. She had a normal weight of 13 kg. Local examination showed a mass at the anterior neck more on the left half, measured 4 cm × 4 cm, no skin changes, no discharge. There was differential warmth and tenderness. It was fluctuant and moves with swallowing. Thyroid ultrasound scan showed normal right lobe; left thyroid gland is enlarged to 4.52 cm × 3.37 cm with a heterogenous echo texture. Thyroid function test was in keeping with euthyroid sick syndrome: TSH 0.3 (0.5-3.7 mIU/L); fT3 0.3 (1.4-4.2 pg/ml); fT4 1.4 (0.8-2.0 pg/ml). An assessment of acute suppurative thyroiditis was made and patient was treated with I.V. Cefuroxime and metronidazole, and by the 5th day on antibiotics, a portion of the swelling had become overtly hyperemic and begun to exude pus. The abscess was incised and 4 ml of frank pus was drained. Microscopy, culture and sensitivity of the aspirate revealed klebsiella sensitive to ciprofloxacin, ofloxacin and amoxyl-clavulanic acid. Child’s condition improved significantly thereafter and she has since been discharged home and doing well. Thus prompt diagnosis and treatment is vital. Pyriform sinus fistula should be suspected in all paediatric cases.